Communicating The Word ofGod - Wijngaards, John N. M. (Communicatio socialis, 1979)
The Ward of God is addressed to people, to individualsand communities. To understand what this means in concrete circumstances, consider for a moment the following typical communities in Andhra Pradesh, lndia. Mutluru in Guntur District: 1350 persons, practically all Catholics; caste people, mainly Reddy. The village was founded by a Catholic community that goes back to the 18th century; now parish headquarters with primary school, high school and dispensary. Community composed of small farmers; literacy 37%; per capita income a month Rs 32. Personnel: one priest, five sisters, 16lay teachers. (...)